A Neutrosophic Approach to Analyzing Determining Factors in RIMPE Tax Collection in Ecuador - Myrian del Rocío Hidalgo Achig; Mayra Alexandra Chicaiza Herrera; Bryan Marcelo Barragán Pazmiño (Neutrosophic Sets and Systems)
This study analyzed the factors influencing tax collection under the RIMPE regime in Ecuador, applying neutrosophic logic to address the uncertainty and ambiguity inherent in decision-making within fiscal analysis. The employed methodology included an adaptation of the ELECTRE I method with bipolar neutrosophic numbers, en abling the integration of diverse perspectives into the decision-making process. The results obtained highlighted the simplicity of the regime and the control of the SRI as the most influential factors in fiscal revenue collection. The approach applied in the study facilitates a more accurate and efficient evaluation of fiscal policies, promoting greater equity and efficiency in the tax system.